Exploring Self-Efficacy, Attitude and Teaching Motivation as Predictors of ESP Teaching Intention among Pre-Service Early Childhood Teachers - Yuniarti Yuniarti; Ryani Yulian (Universitas Pendidikan Ganesha, 2026)
The growing demand for professional early childhood teachers capable of integrating English instruction has increased the need for educators with strong pedagogical and psychological readiness. However, research exploring pre-service teachers’ intention to teach English for Specific Purposes (ESP) in early childhood contexts remains limited, especially in non-English-major programs where English is taught as a supporting subject. This study investigated the mediating role of teaching motivation in the relationship between self-efficacy, attitude, and the intention to teach ESP among pre-service early childhood teachers. A total of 100 pre-service teachers from the Early Childhood Education Department at Universitas Muhammadiyah Pontianak participated in this study. Data were obtained through structured questionnaires and examined using the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach. The results show that both self-efficacy and attitudes significantly affect teaching motivation, which in turn strongly predicts the intention to teach ESP. Teaching motivation also mediates the relationships between self-efficacy, attitude, and teaching intention. These findings emphasize the crucial role of motivation as a psychological bridge linking teachers’ beliefs and attitudes with their teaching intentions. The study enriches the existing research on ESP teacher preparation by highlighting the importance of motivational and affective factors in early childhood teacher education, and it suggests that teacher education programs should strengthen self-efficacy, foster positive attitudes, and enhance teaching motivation to better prepare professional early childhood teachers for effective ESP instruction.